Optimization of the production of xylanases in corncob-based media by Aspergillus niger and Trichoderma longibrachiatum using Taguchi approach - Elegbede, Joseph Adetunji; Lateef, Agbaje (Acta Biologica Szegediensis, 2019)
Xylanases are important in producing several commercially valued bioproducts. In this study, xylanases were produced by Aspergillus niger L3 and Trichoderma longibrachiatum L2 using corncob, an agricultural waste, as sole carbon source. The impact of important fermentation parameters at individual and interactive levels were studied using Taguchi L9 orthogonal array. Substantial variation in enzyme synthesis was observed among designated factor levels. The optimal conditions to produce xylanases were 20% inoculum size, 24 h fermentation time, substrate concentration of 15 g/l at pH 5.5 for A. niger L3; and inoculum size 12.5%, 72 h fermentation time, substrate concentration of 15 g/l at pH 5.5 for T. longibrachiatum L2. Validation of outcomes of the optimal combination of parameters resulted in a significant improvement of approximately 208.09 and 192.59% in the yield of xylanase by A. niger L3 (28.69 to 88.39 U/ml) and T. longibrachiatum L2 (22.13 to 64.75 U/ml), respectively. The study therefore established the optimal valorization of corncob to produce xylanase by the fungal isolates.